Factors Associated with Poor Quality of Life in a Canadian Cohort of Patients with Inflammatory Bowel Disease: A Cross-sectional Study. Issue 2 (16th May 2020) - Nazarian, Amir; Bishay, Kirles; Gholami, Reza; Scaffidi, Michael A; Khan, Rishad; Cohen-Lyons, Daniel; Griller, Nadia; Satchwell, Joshua B; Baker, Jeffrey P; Grover, Samir C; Irvine, Elizabeth Jan
Abstract: Background: Health-related quality of life (QoL) is often adversely affected in patients with inflammatory bowel disease (IBD). We aimed to identify factors associated with poor QoL among Canadian patients with IBD in clinical remission. Methods: We enrolled patients at a single academic tertiary care center with inactive IBD. All eligible patients completed a series of questionnaires that included questions on demographics, disease activity, anxiety, depression and the presence of irritable bowel syndrome (IBS) symptoms. Stool sample for fecal calprotectin (FC) was also collected to assess for subclinical inflammation. The primary outcome measure was QoL assessed by the short inflammatory bowel disease questionnaire (SIBDQ), with planned subgroup comparisons for fatigue, anxiety, depression and IBS symptoms. Results: Ninety-three patients were eligible for inclusion in this study. The median SIBDQ scores were lower in patients with anxiety ( P < 0.001), depression ( P = 0.004), IBS symptoms ( P < 0.001) and fatigue ( P = 0.018). Elevated FC in patients in clinical remission did not impact QoL. These findings were consistent on multivariate linear regression. Conclusions: Anxiety, depression, fatigue and IBS symptoms are all independently associated with lower QoL in patients with inactive IBD. Clinicians are encouraged to screen for these important factors as they may detrimentally impact QoL in IBD patients even in clinical remission.